Kemampuan Penalaran Adaptif Melalui Model Reciprocal Teaching pada Logika Matematika dan Himpunan - Dwi Oktaviana; Rahman Haryadi (SAP (Susunan Artikel Pendidikan), 2020)
The purpose of this study is to determine the improvement of students’ adaptive reasoning abilities through the reciprocal teaching model. This research is experimental research with one group pretest-posttest design. The sample in this study were first semester students of class B IKIP PGRI Pontianak with cluster random sampling technique. The data analysis technique used descriptive statistics and inferential to test whether there was an increase in adaptive reasoning skills through the reciprocal teaching model. The results showed that the students obtained the initial test score with an average of 21,23 while the final test score with an average of 71,36. After applying the reciprocal teaching model to the students’ adaptive reasoning ability, they obtained a sig. 0,000 where sig. < 0,05 (?). Thus the reciprocal teaching model can improve students’ adaptive reasoning abilities.